Mobile Game Based Chemical Bond Learning Application - Kholid Fathoni; Rizky Yuniar Hakkun; Wildan Andaru (Universitas PGRI Madiun, 2020)
Mobile game technology is growing rapidly and this is directly proportional to the increasing number of mobile games in circulation. The growing market of the mobile game industry is not accompanied by the number of games that have educative content in them. The challenging, fun, and addictive nature of the game has a negative impact if no educational content is provided. Therefore, educational content needs to be present in a game so that the game can have a positive impact on the players. This research makes a chemical educational game to study chemical bonding material that aims as an interactive learning media for students and the general public. This game is made based on mobile with 2D characters consisting of 5 levels. Level 1 contains material for salt compounds, level 2 contains material for acid compounds, level 3, 4 and 5 contains material for basic compounds. The results of this game trial show that all the features of this game application run well, can be run on several smartphones, and most users from 20 audiences stated that this game is comfortable and easy to use.